Scientific collaboration analysis of Brazilian postgraduate programs in information science - da Silva Justino, Thais; Morato do Amaral, Roniberto; Lopes de Faria, Leandro Innocentini; Cardoso de Brito, Aline Grasiele (AWARI, 2021)
Due to the growing interest in metric studies on the scientific collaboration of national postgraduate studies, together with the theoretical and applied bases of Information Science supported by metric studies of information, it became relevant to identify how scientific collaborations occur in postgraduate programs in Information Science. The research method included the use of bibliometrics and social network analysis as an information analysis technique. The sample involved 519 articles from 421 permanent professors working in 27 Postgraduate Programs (PP), from 2013 to 2018. The results achieved included the elaboration of a set of indicators that denote scientific collaboration activities; In short, interpersonal relations networks are relevant to the internationalization of the Information Science area, and internationalization is fundamental for the development of programs. It was concluded that the results achieved can contribute to the improvement of the PPG and the National Postgraduate System, by maximizing the understanding of collaboration in Information Science.